SISTEM PENGUKURAN KADAR GAS SO2 SECARA JARAK JAUH UNTUK PEMANTAUAN PADA KAWASAN GUNUNG BERAPI - Arlien Siswanti; Figur Humani; Agus Sulistiyo; Inayatul Inayah; Giga Verian Pratama; Jatmiko Endro Suseno (Youngster Physics Journal, 2014)
When a forest fire or volcanic eruption must be accompanied by the emergence of gases endanger human health. By utilizing SO2 gas sensor and telemetry system,they are effectively used for the benefit of monitoring gas levels affected areas. The method used  by a field study in Gedong Songo which is now in an active condition give off gases which are still not detected. Through SO2 gas senso gas levels that can be obtained gas levels is 3.57 ppm. All data obtained from sensors will be transmitted in real time to ground stations via the telemetry system. Results of SO2 gas concentration data transmission will be shown through the android app and then analyzed as a follow up of disaster management.Keywords: Disaster, Quadcopter, gas sensors, Telemetry, Android.